1993
DOI: 10.1021/bi00080a034
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies for fluorescent molecular rotors

Abstract: We have prepared monoclonal antibodies for the fluorescent molecular rotors 9-(2-carboxy-2-cyanovinyl)julolidine (CCVJ) and 9-(dicyanovinyl)julolidine (DCVJ). Mouse monoclonal antibody (IgG2b) prepared against CCVJ-conjugated bovine serum albumin strongly bound CCVJ and DCVJ. The CCVJ (or DCVJ) binding to IgG and Fab was accompanied by a drastic increase in fluorescence quantum yield, suggesting the restriction of intramolecular rotational relaxation about the donor-acceptor bond of the fluorophores. Nonspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 21 publications
4
80
0
1
Order By: Relevance
“…Of particular interest are some dyes with segmental mobility that are capable of an intramolecular twisting motion in the excited state [6], which are often referred to as "molecular rotors" [7,8]. Those molecules have two competing deexcitation pathways: (a) a pathway in which the molecule remains in a planar conformation when it returns to the ground state, and (b) a pathway in which the molecule assumes a twisted state before returning to the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are some dyes with segmental mobility that are capable of an intramolecular twisting motion in the excited state [6], which are often referred to as "molecular rotors" [7,8]. Those molecules have two competing deexcitation pathways: (a) a pathway in which the molecule remains in a planar conformation when it returns to the ground state, and (b) a pathway in which the molecule assumes a twisted state before returning to the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the fluorescence lifetime for another malononitrile, 9-(2-carboxy-2-cyanovinyl)julolidine (CCVJ) increased by more than a factor of 5 upon binding of an antibody. [34] Functionalising a similar molecule with a hydrophobic Figure 1. Example ground-(S 0 ) and excited-state (S 1 ) potential energy surfaces for a molecular rotor as a function of intramolecular torsional angle.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 Increased glycerol content is known to increase viscosity with only minimal changes of solvent polarity. 10 Glycerol contents of 40, 50, 60, 70, and 80% resulted in viscosities of 72, 109, 165, 248, and 374 mPa‚s, respectively.…”
mentioning
confidence: 99%